BS EN IEC 62271-207. High-voltage switchgear and controlgear. Part 207. Seismic qualification for gas-insulated switchgear assemblies, metal enclosed and solid-insulation enclosed switchgear for rated voltages above 1 kV (1st January 2021) - British Standards Institution
No abstract available